2023
DOI: 10.1186/s40100-023-00258-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of food governance for alternative and sustainable food systems: a systematic review

Aintzira Oñederra-Aramendi,
Mirene Begiristain-Zubillaga,
Mamen Cuellar-Padilla

Abstract: Despite the various studies on food governance structured around alternative food systems (AFS), analysis of the essential characteristics of it which facilitate the sustainability of the food system (FS) is still incipient. This study aims to clarify the debate on the role of governance in sustainability of the FS by way of the following two objectives: (i) to characterise the analytical approach of the literature in the processes of structuring of food governance related to AFS, and (ii) to reflect qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 152 publications
0
7
0
Order By: Relevance
“…Several models and frameworks were designed to identify and analyze actors involved in food systems governance interactions and processes [81,83,85,88,92,98,100,101]. Some were developed as tools to improve or enhance agri-food value chains [82,106], promote sustainable food enterprises and entrepreneurship [91,103,108], support food finance architecture that incorporates health, environmental, and societal concerns into financial decision-making; and strengthen economic development and stability for food systems governance [113,114] (Supplemental Table S1).…”
Section: Purpose and Application Of The Framework And Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several models and frameworks were designed to identify and analyze actors involved in food systems governance interactions and processes [81,83,85,88,92,98,100,101]. Some were developed as tools to improve or enhance agri-food value chains [82,106], promote sustainable food enterprises and entrepreneurship [91,103,108], support food finance architecture that incorporates health, environmental, and societal concerns into financial decision-making; and strengthen economic development and stability for food systems governance [113,114] (Supplemental Table S1).…”
Section: Purpose and Application Of The Framework And Modelsmentioning
confidence: 99%
“…Fifteen sources discussed multistakeholder governance, of which five sources described shared collaborative governance models [83,90,96,98,99], and two sources discussed co-governance models [83,101]. Clark et al (2021) described a governance engagement continuum 2.0 model [83], adapted from the corporate food regime and food movements framework developed by Holt Giménez and Shattuck 2011 [89] and Andrée et al (2019) [13], which discussed three forms of governance (i.e., multi-stakeholder, co-governance, and self-governance) to show how social movement organizations could create new deliberative governance spaces through convening to change power dynamics.…”
Section: Types Of Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, several recent reviews on the governance of agri-food systems showed that it is under-researched, and there are multiple issues in the research in this area [1,13,15,21,25,26]. Still, there is no common approach for defining the content and components of a governance system, and an acceptable framework for a comprehensive assessment of the governance is lacking.…”
Section: Of 17mentioning
confidence: 99%
“…Food security, when viewed from a global perspective, encompasses both the sustainable production of high-qual-the planet's population [10]. Despite various food management studies structured around alternative food systems, analysis of the main characteristics that contribute to food system sustainability has not yet been comprehensively explored [11]. Food systems include the production, transportation, processing, and consumption of food, including food loss and waste.…”
Section: Introductionmentioning
confidence: 99%